ANALISIS FRONT END SISTEM INFORMASI WEBSITE PT. BALI SWAKINARYA CIPTA SEJAHTERA DENGAN METODE SYSTEM USABILITY SCALE - Agustina, Ni Kadek Vira; Putra, I Nyoman Tri Anindia (JURNAL TEKNIK INFORMATIKA, 2021)
Abstract— System analysis is a description of an information system that has not been changed in various components which aims to evaluate a problem or obstacle that will occur in the system so that it can be repaired or developed. This study aims to evaluate a website information system that has just been created by the company and to obtain recommendations in order to develop the website. Website is a medium for conveying information to the public. The System Usability Scale (SUS) is one of the most popular, effective and inexpensive usability testing methods. SUS can also measure perceived usefulness using a questionnaire. This study used a questionnaire with the System Usability Scale (SUS) method to get 100 respondents in order to find out the satisfaction of users of the PT. Bali Swakinarya Cipta Sejahtera. The results of this study determine user responses and can be used to develop and improve systems so that they provide clear and precise information to users.